A Crossover Study From a Gender Perspective: The Relationship Between Job Insecurity, Job Satisfaction, and Partners’ Family Life Satisfaction - Emanuel, Federica; Molino, Monica; Presti, Alessandro Lo; Spagnoli, Paola; Ghislieri, Chiara (Frontiers in Psychology, 2018)
Background: In the last years, many changes have involved the labor context: new ways of working, more flexibility and uncertainty, new and more insecure job contracts. In this framework, perceived job insecurity, worker’s perception about potential involuntary job loss, has received renewed interest, also for those workers with a permanent contract in Italy. Consequences of job insecurity on work-related outcomes such as job satisfaction have been demonstrated; nevertheless, its possible effects outside the workplace seem to be underestimated so far. Moreover, literature highlighted the importance to consider gender as a possible moderator in the relationship between one partner’s stressors and the other partner’s strain. Aim: According to spillover and crossover theories, this study aim was to investigate the relationship between job insecurity and family life satisfaction of both partners, through the mediation of job satisfaction. The model has been simultaneously tested in two groups, women and men, in a sample of permanent workers. Method: The research involved a convenience sample of 344 employees with permanent contract (53% female) from different occupational sectors. Participants (focal persons) and their partners filled out a self-report questionnaire. Results: The multi-group SEM indicated a full mediation of job satisfaction in the relationship between job insecurity on the one side, and both individual’s and his/her partner’s family life satisfaction on the other side in both groups. Conclusion: These study findings highlighted how job insecurity may be indirectly and negatively related to both members’ family life satisfaction, through the mediation of job satisfaction. As regards gender, similar spillover and crossover patterns emerged, contributing to that literature that highlights a greater similarity in the models of interaction between work and family among women and men. Interventions should be aimed at reducing perception of job insecurity among workers, including those with permanent contract. Employers should improve communication and flow of information about future organizational changes. Moreover, interventions useful to monitor and reinforce employees’ job satisfaction should be planned. Finally, career practitioners may provide counseling and coaching projects aimed at strengthening employees’ employability and their ability to deal with changes.